The Influence of Green Marketing Mix, Green Trust, Environmental Value, and Green Knowledge on Attitude-Mediated Repurchase Intention on Eco-Friendly Skincare Products in Indonesia - Yosepha Naftali Ananta; Anna Amalyah Agus (Green Publisher Indonesia, 2025)
This research examines the factors influencing consumer repurchase intention for eco-friendly skincare products in Indonesia, focusing on the role of green marketing mix elements and environmental factors. This study aims to analyze the influence of green product, green price, green place, green promotion, green trust, environmental value, and green knowledge on repurchase intention, with attitude as a mediating variable. As consumer awareness of sustainability issues continues to rise, the skincare industry in Indonesia is increasingly required to adopt green marketing strategies to strengthen competitiveness through repurchase intention. A quantitative approach with an explanatory research design was employed. The sampling technique used was purposive sampling, while the sample size was determined based on Green’s (1991) formula. Data were analyzed using path analysis to examine the causal relationships among the studied variables. The results indicate that all proposed hypotheses are supported. These findings confirm that green marketing elements significantly influence repurchase intention, both directly and indirectly through the mediation of consumers’ positive attitudes toward environmentally friendly products. The managerial implications of this study offer strategic insights for skincare companies in formulating policies that support sustainable product development and enhance consumers' environmental literacy. A deeper understanding of green consumer behavior dynamics enables companies to craft more adaptive, competitive, and sustainability-oriented marketing strategies in the long term.